Additions to The Herpetofauna of Pasoh Forest Reserve, Negeri Sembilan, Peninsular Malaysia - Chan Kin Onn,; Mohd. Shahfiz Azman,; Nor Azlin,; Pan Khang Aun, (Tropical Life Sciences Research, 2009)
A survey was carried out at the Pasoh Forest Reserve from 13–19 December, 2007 and 20–24 January, 2008, to inventory the herpetofauna contained therein. A total of 23 species of reptiles and amphibians were collected during this survey, five of which have not previously been recorded in the Pasoh Forest Reserve. An updated checklist which incorporates findings from previous studies is presented. Satu survei herpetofauna telah dijalankan di Hutan Simpan Pasoh dari 13–19 Disember 2007 dan 20–24 Januari 2008. Sebanyak 23 spesies reptilia dan amphibia berjaya dijumpai, termasuk lima spesies yang merupakan rekod baru untuk Hutan Simpan Pasoh. Senarai spesies terbaru yang juga mengandungi hasil kajian-kajian lepas disediakan.